INTERAKSI SOSIAL WARGA BELAJAR PAKET C DI PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) BINA EDUKASI JL. ARIFIN AHMAD PEKANBARU - ', Harismanto Harismanto; Baheram, Murni Baheram Murni; Jas, Jaspar Jas Jaspar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract. The purpose of this study was to determine the level of social interactionresidents learn C packet in community learning center (PKBM) EducationDevelopment Jl. Arifin Ahmad Pekanbaru. Research site is at the CommunityLearning Center (PKBM) Education Development Jl. Arifin Ahmad Pekanbaru.This is a descriptive study with a quantitative approach that aims to provide asystematic overview about the state of ongoing research on the object that is thesocial interaction residents learn C packet in community learning center (PKBM)Education Development Jl. Arifin Ahmad Pekanbaru. The population in this studywas residents learn at Education Development Center PKBM activities wereidentified amounted to 55 people. Samples were determined in this study were 35people. From the calculation results of the study questionnaire, obtainedinformation that the acquisition of the percentage of citizens studying socialinteraction, it is known that residents learn social interaction C packet incommunity learning center (PKBM) Education Development Jl. Arifin AhmadPekanbaru get a percentage of 81.9% with a very good category. The mean valueper indicator can be seen that, on the communication aspects of obtaining thehighest mean score of 3.1 and 0.7 sd with high interpretation, then the meanaspect attitude 3.0 sd 0.7, then the behavioral aspects of the group obtained amean 3.0 sd 0.7, and aspects of the social norms of the mean 3.1 and sd 0.8. If intotal the overall mean per indicator and divide by the number of indicators can beseen the average number of mean 3.0 and sd 0.7 is high. After doing research anddata processing result can be concluded that residents learn have to interact withthe C packet well.Keywords: social interaction residents learn